1989
DOI: 10.3109/02713688908997572
|View full text |Cite
|
Sign up to set email alerts
|

Anin vitroAnalysis of Aminoglycoside Corneal Epithelial Toxicity

Abstract: We evaluated the cytotoxicity of four aminoglycoside agents (neomycin, gentamicin, tobramycin, and amikacin) using an in vitro confluent rabbit corneal epithelial cell culture model. Primary corneal epithelial cell cultures were established and cells replated at 2 x 10(4) cells/2 cm2 well. After 48 hours either vehicle or an antibiotic was added at varying concentrations, each for 5, 30, or 60 minutes. 3H-thymidine was added immediately after drug removal and incorporation was measured 8 hours after drug or ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…In fact, after an exhaustive analysis of the literature it can be concluded that aminoglycosides (gentamicin and tobramycin), when used at their commercially available concentrations of 3.0 mg/mL, have only a moderate or even no toxic effect on rabbit corneal epithelial cells or keratocytes (6)(7)(8)(9)(10)(11). Although many other studies conclude for an aminoglycoside toxicity, such conclusions should be carefully considered because several experiments have actually been conducted with an antibiotic concentration much higher than that used in the clinical practice (.10 mg/mL versus 3.0 mg/mL) (6,8,13) or with commercial eye drops containing preservatives (11,14,15), whose negative influence on the cell integrity is well-known (16)(17)(18)(19)(20). Therefore only 2 reports are available up to date describing a real corneal toxicity for gentamicin (but not for tobramycin) (7,12).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In fact, after an exhaustive analysis of the literature it can be concluded that aminoglycosides (gentamicin and tobramycin), when used at their commercially available concentrations of 3.0 mg/mL, have only a moderate or even no toxic effect on rabbit corneal epithelial cells or keratocytes (6)(7)(8)(9)(10)(11). Although many other studies conclude for an aminoglycoside toxicity, such conclusions should be carefully considered because several experiments have actually been conducted with an antibiotic concentration much higher than that used in the clinical practice (.10 mg/mL versus 3.0 mg/mL) (6,8,13) or with commercial eye drops containing preservatives (11,14,15), whose negative influence on the cell integrity is well-known (16)(17)(18)(19)(20). Therefore only 2 reports are available up to date describing a real corneal toxicity for gentamicin (but not for tobramycin) (7,12).…”
Section: Discussionmentioning
confidence: 98%
“…However, the currently available published studies do not support such conclusion. In fact most of the published data indicate that aminoglycosides at the concentrations normally used in the clinical setting (3 mg/mL) have minimal or even no toxicity for the corneal epithelium or keratocytes (6)(7)(8)(9)(10)(11). Nevertheless, both Nelson et al (7) and Alfonso et al (12) described a significant corneal toxicity for gentamicin (but not for tobramycin).…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…5,6,25,26,29 Conversely, aminoglycosides are usually described as highly toxic regardless of the conflicting results available in the literature. In fact, most of the published studies suffer from several drawbacks such as the use of fortified antibiotic concentrations 13,16,19 or the concomitant presence of preservatives, 17,20,21 whose negative influence on cell integrity is well known. [8][9][10][11]14,16,21 Netilmicin is a third-generation aminoglycoside that has excellent in vitro and in vivo activity against the most common bacterial ocular pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Results of in vitro studies on rabbit and human corneal epithelial cell cultures indicate that certain antibiotics, antiviral drugs, and the preservatives found in many ophthalmic antibiotic preparations are more toxic to the migrating epithelium than others. [3][4][5][6][7] The purpose of the study reported here was to determine whether antibiotics have a detrimental effect on the morphologic characteristics and migration of canine corneal epithelial cells in culture. We evaluated the effects of commonly used ophthalmic antibiotics on the canine corneal epithelium in vitro.…”
mentioning
confidence: 99%